Haplopacha (Lepidoptera: Lasiocampidae) reviewed: four new species, first descriptions of the genitalia of both sexes, and unique alar scale organs - Dupont, Steen; Simonsen, Thomas J.; Zilli, Alberto (Zootaxa, 2016)
The collection of five specimens of Haplopacha at Ndumo Nature Reserve in South Africa highlights unknown species diversity in the monotypic genus. A total of four new species; H. riftensis sp. nov., H. tangani sp. nov., H. lunata sp. nov. and H. ndoumoi sp. nov., were identified in the Natural History Museum of London collection and the study of fresh specimens also revealed the presence of uniquely characteristic alar scale patches absent from the original species description of the genus type species H. cinerea. Based on the new species the descriptions of Haplopacha is amended. The identification of the new species was done using conventional light microscopy and scanning electron microscopy of the general morphology, wing venation and genitalia observations.